Air Pollution Concentrations and Their Determinants in The Top Ten Most Polluted Countries in The World In 2010-2020 - Dennys Ilham Sugiarto; Sri Rahayu Budi Hastuti (AIBPM Publisher, 2024)
This study analyzes air pollution concentration and its determinants in ten countries with the highest levels of air pollution from 2010 to 2020. Air pollution has become a global issue affecting both human health and the environment. The study uses secondary data and applies two analytical tools: a concentration index to identify countries with the highest air pollution levels, and panel data regression to analyze its determinants. Air pollution is proxied by CO2 emissions. The results indicate that eight out of ten countries have a concentration index greater than one, with Japan, South Korea, and Germany ranking as the top three countries with the highest air pollution concentrations. The population variable has a positive and significant impact on air pollution concentration in these countries. Conversely, the energy consumption variable has a negative and significant effect on air pollution concentration. On the other hand, economic growth does not have a significant effect on air pollution concentration. The study's implications highlight the need for a transition to more efficient and renewable energy sources as a crucial step in reducing the negative impacts of air pollution. Stricter environmental policies and increased investments in eco-friendly technologies are highly recommended to address this issue